Lawyering peace - Williams, Paul R. 1965- (Cambridge University Press, 2021)
In all but the rarest circumstances, the world's deadly conflicts are ended not through outright victory, but through a series of negotiations. Not all of these negotiations, however, yield a durable peace. To successfully mitigate conflict drivers, the parties in conflict must address a number of puzzles, such as whether and how to share and/or re-establish a state's monopoly of force, reallocate the ownership and management of natural resources, modify the state structure, or provide for a path toward external self-determination. Successfully resolving these puzzles requires the parties to navigate a number of conundrums and make choices and design mechanisms that are appropriate to the particular context of the conflict, and which are most likely to lead to a durable peace. Lawyering Peace aims to help future negotiators build better and more durable peace agreements through a rigorous examination of how other parties have resolved these puzzles and associated conundrums